GSK-3β and BDNF genes may not be associated with venlafaxine treatment response in Chinese of Han ethnicity - Sun Q (Dove Medical Press, 2019)
Qianqian Sun,1,2 Fan Yuan,1,2 Decheng Ren,1,2 Gaini Ma,1,2 Fengping Yang,1,3 Xi Wu,1,3 Lin He,1,3 Guang He1,21Bio-X Institutes, Key Laboratory for the Genetics of Developmental and Neuropsychiatric Disorders (Ministry of Education), Shanghai Jiao Tong University, Shanghai 200030, P.R. China; 2Shanghai Key Laboratory of Psychotic Disorders, Shanghai Institute of Mental Health, Shanghai Jiao Tong University, Shanghai 200030, P.R. China; 3Institute for Nutritional Sciences, Shanghai Institutes of Biological Sciences, Chinese Academy of Sciences, Shanghai 200031, P.R. ChinaPurpose: Venlafaxine is one of the commonly prescribed antidepressants for major depressive disorder (MDD). Accumulated evidence revealed the involvement of glutamatergic system in the pathophysiology of MDD and antidepressant treatment. Methods: We recruited 193 MDD patients who have been taking venlafaxine for 6 weeks, and investigated whether single nucleotide polymorphisms (SNPs) in GSK-3β and BDNF were associated with treatment response. Nine SNPs were selected randomly depending on association studies. Efficacy of treatment was determined by 17-item Hamilton Rating Scale. Allele and genotype frequencies were compared between responders and nonresponders.Results: After adjusting the false discovery rate, no significant difference was observed between response and nonresponse groups in allele or genotype distributions after venlafaxine treatment for 6 weeks.Conclusion: Our results indicated that genetic variants in the GSK-3β and BDNF may not be associated with treatment response in MDD patients treated with venlafaxine.Keywords: association, GSK-3β, BDNF, major depressive disorder, venlafaxine